Digital marketing in the e-commerce of the wholesale hardware branch of Venezuela (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
This article is the product of a research whose general objective was to analyze digital marketing in electronic commerce of the Wholesale Hardware branch of Venezuela. It was framed in the positivist paradigm, quantitative approach, type of field and descriptive level. The study population was made up of thirteen (13) companies that market new products in the wholesale hardware branch of Venezuela, specifically in the Category: Tools and Construction, through the Mercado Libre Venezuela page, for its part, the sample is intentional non-probabilistic type, because some criteria were taken to determine it, for this reason it was made up of six (6) companies, which represents forty-six percent (46%) of the study population, it was also decided to take as a source of information to the Marketing and Sales Managers of these marketing units. Data collection was carried out using the survey technique. The instrument that was applied was a questionnaire and was designed based on the Likert scale model, which was validated using the technique called expert judgment, taking into account the coherence of the questions with the objectives of the research, as well as the relevance of the same and clarity in the wording. The reliability of the instrument was determined through Cronbach's Alpha coefficient with 0.919. After applying the questionnaire to the selected sample, the data was organized to be presented in tables and bar graphs and the respective analyzes were carried out, which allowed the author to determine the conclusions of the study and the recommendations, according to the specific objectives formulated.
Keywords: e-commerce; globalization; wholesale hardware; digital marketing